2022
DOI: 10.1186/s12890-022-02262-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of ferroptosis in chronic intermittent hypoxia-induced lung injury

Abstract: Purpose Chronic intermittent hypoxia (CIH) causes lung injury but the mechanism is unclear. Ferroptosis is a novel form of programmed cell death. In this research, we attempted to explore the role of ferroptosis in CIH-induced lung injury both in vitro and in vivo. Methods Sprague-Dawley rats were randomly separated into control group, CIH group and CIH + ferrostatin-1 group (CIH + Fer-1). Rats in the CIH group and CIH + Fer-1 group were exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Chronic intermittent hypoxia is the main clinical feature of OSA patients. Chen et al ( 39 ) reported chronic intermittent hypoxia induced intracellular ROS accumulation, which leads to ferroptosis. Simultaneously, DEmRNAs-enriched signaling pathways (such as Wnt signaling pathway, MAPK signaling pathway, and Calcium signaling pathway) are also involved in the regulation of ferroptosis ( 23 , 40 , 41 ), so we speculated that ferroptosis-related genes are the molecular targets of CPAP treatment of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic intermittent hypoxia is the main clinical feature of OSA patients. Chen et al ( 39 ) reported chronic intermittent hypoxia induced intracellular ROS accumulation, which leads to ferroptosis. Simultaneously, DEmRNAs-enriched signaling pathways (such as Wnt signaling pathway, MAPK signaling pathway, and Calcium signaling pathway) are also involved in the regulation of ferroptosis ( 23 , 40 , 41 ), so we speculated that ferroptosis-related genes are the molecular targets of CPAP treatment of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Fer-1 is a widely utilized small molecule inhibitor of ferroptosis in laboratory settings. It has been reported to upregulate GPX4 expression and impede the progression of PF [166][167][168]. However, its unfavorable pharmacokinetic profile renders it unsuitable for clinical application [20].…”
Section: Clearance Of Lipid Peroxidesmentioning
confidence: 99%
“…Ferroptosis can also be induced in normal cells under hypoxia conditions. It was reported that chronic intermittent hypoxia (CIH) induced ferroptosis in the hippocampus, lung, liver, and cardiomyocytes by downregulating NRF2 and GPX4, as well as upregulating ACSL4, leading to cognitive impairment and injury of brain, lung liver, and heart [ 122 , 123 , 124 , 125 ]. In the brain, hypoxic-ischemic induces ferroptosis with the increased TFRC expression, and decreased expression of SLC7A11, TRX-1, and GPX4 [ 126 , 127 , 128 ].…”
Section: The Mechanism and Regulation Of Ferroptosis Modulated By Hyp...mentioning
confidence: 99%